Antileishmanial activity of tetra-cationic porphyrins with peripheral Pt(II) and Pd(II) complexes mediated by photodynamic therapy - Linares, Irwin A.P. [UNESP]; Uría, Maricely Sánchez [UNESP]; Graminha, Marcia A.S. [UNESP]; Iglesias, Bernardo Almeida; Velásquez, Angela M.A. [UNESP] (Elsevier, 2023)
Leishmaniasis is a neglected disease that impacts more than one billion people in endemic areas of the globe. Several drawbacks are associated with the currently existing drugs for treatment such as low effectiveness, toxicity, and the emergence of resistant strains that demonstrate the importance of looking for novel therapeutic alternatives. Photodynamic therapy (PDT) is a promising novel alternative for cutaneous leishmaniasis treatment because its topical application avoids potential side effects generally associated with oral/parenteral application. A light-sensitive compound known as photosensitizer (PS) interacts with light and molecular oxygen to generate reactive oxygen species (ROS), which promote cell death by oxidative stress through PDT approaches. Here, for the first time, we demonstrate the antileishmanial effect of tetra-cationic porphyrins with peripheral Pt(II)- and Pd(II)-polypyridyl complexes using PDT. The isomeric tetra-cationic porphyrins in the meta positions, 3-PtTPyP, and 3-PdTPyP, exhibited the highest antiparasitic activity against promastigote (IC50-pro = 41.8 nM and 46.1 nM, respectively) and intracellular amastigote forms (IC50-ama = 27.6 nM and 38.8 nM, respectively) of L. amazonensis under white light irradiation (72 J cm–2) with high selectivity (SI > 50) for both forms of parasites regarding mammalian cells. In addition, these PS induced the cell death of parasites principally by a necrotic process in the presence of white light by mitochondrial and acidic compartments accumulation. This study showed that porphyrins 3-PtTPyP and 3-PdTPyP displayed a promising antileishmanial-PDT activity with potential application for cutaneous leishmaniasis treatment.
Keywords: Cutaneous leishmaniasis; Leishmania acidic compartments; Leishmania amazonensis; Mitochondria colocalization; Pd(ii) complexes; Photodynamic therapy; Pt(ii) complexes; Tetra-cationic porphyrins